Islamic Law Study (Syafi’i School) on The Fulfillment of Maintenance For Long-Distance Couples in Koncer Kidul Village, Tenggarang Subdistrict, Bondowoso Regency - Mahdum Zahid; Khoirul Anwar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine how the law of fulfilling maintenance for long-distance couples, both material and spiritual, is viewed in Koncer Kidul Village, Tenggarang Subdistrict, Bondowoso Regency, from the perspective of the Syafi’i school of thought. The methodology used is qualitative with a case study approach, where data was collected through in-depth interviews, field observations, and documentation studies. The research results indicate several legal considerations regarding the fulfillment of maintenance for long-distance couples in the village, influenced by factors such as needs and existing debts. It is hoped that this research can serve as a consideration for the community to carefully think about engaging in long-distance relationships. Keywords: , , Maintenance Fulfillment, Long-Distance Couples